THE NEO-KANTIAN NOTION OF WE-SUBJECT BETWEEN PHENOMENOLOGY AND ANALYTICAL PHILOSOPHY SOME PRELIMINARY REMARKS - Redaelli, Roberto (Etica e Politica/Ethics and Politics, 2021)
This paper examines Rickert's reflection on ethics, with a special focus on the notion of WirGemeinschaft, and assesses its relevance to the current philosophical debate on the sources of moral normativity. To this purpose the paper firstly examines the social notion of self developed by Rickert against solipsistic theories in ethical and theoretical fields. The second point is to bring to light the presence of a thought of the other in Rickert's philosophy: albeit this proposition is apparently reminiscent of certain virtuous phenomenological positions recognizable in the current debate on sources of normativity, yet it does break away from it on account of the symmetry it establishes between the I and the you. Finally, on the basis of these inquiries, I conclude attributing to Rickertian philosophy a theory of normativity in the first-person-plural (We) featuring a radical redefinition of the Kantian notion of autonomy in the social sense.
CRIS-Team WoS Importer:2021-08-27